THE IMPLEMENTATION OF MULTIPLE INTELLIGENCE ON THE INPUT, PROCESS, AND OUTPUT OF ENGLISH LEARNING - Dedi Hasnawan (Universitas Majalengka, 2019)
This research aims at: (1) describing the implementation of Multiple Intelligences on the input, process, and output of English Learning in the Kinesthetic Intelligence Class at SD Immersion Ponorogo, (2) identifying the difficulties in implementing Multiple Intelligences (3) finding out the solutions offered by teacher to overcome the difficulties. This research applied a case study method as one of qualitative research. The data were collected through non-participant observation, interview, and documentation. In analyzing the data, the researcher used interactive model of analysis data by Miles and Huberman. The findings of the research reveals that: (1) the implementation of Multiple Intelligences at SD Immersion covers three aspects; the first is the use of MIR to observe the students’ intelligence characteristic as a reference for the teacher to design the teaching process, the second is the process of teaching/learning which was designed based on the students’ characteristic of intelligences, the third is the process of evaluation and assessment which focused on the students’ performance during the learning activity, (2) the difficulties found on implementing Multiple Intelligences are the creativity of the teacher in designing the lesson plan, material, and media, the difficulty in controlling the kinesthetic students’ behavior, and the time management for the preparation and activities for the students, and (3) the solutions offered by teacher to overcome the difficulties are the use of online resources as the reference to design the learning materials and media, and the use of guiding and assessment during the process of learning to control the students’ behavior.